A note on systems intelligence in knowledge management. Issue 4 (8th May 2017) - Sasaki, Yasuo
Abstract : Purpose: This paper aims to show that systems intelligence (SI) can be a useful perspective in knowledge management, particularly in the context of the socialization, externalization, combination and internalization (SECI) model. SI is a recently developed systemic concept, a certain kind of human intelligence based on a systems thinking perspective. Design/methodology/approach: This paper first provides an overview of the related literature, and then conceptually discusses the role of SI in organizational knowledge creations. Findings: SI can work as a powerful momentum in each stage as well as the whole process of SECI. Originality/value: This paper is the first application of SI to the field of knowledge management. It provides us with a new perspective to touch human factors in knowledge management processes, which are considered to be essential in the SECI model.